Estimating demand spillovers of EU Cohesion Policy using European regional input-output tables - Roman Römisch (The Vienna Institute for International Economic Studies (wiiw), 2020)
This paper develops a simple method to consistently break down world input-output tables to regional input-output tables. They are used to estimate Cohesion Policy-induced demand spillovers in the EU, covering the years 2007-2018. Results indicate that Cohesion spillovers from less developed regions to other regions exceed 40% of their initial EU support in some cases. In addition, spillovers from the more developed regions are equivalent to 24% of their initial EU support. This shows that the existing trade and investment linkages across the EU regions are strong and not only run from less developed to more developed regions but also vice versa. Our results are good news for the net paying regions in the EU. Taking into account capacity growth effects, Cohesion Policy spillovers might well be a multiple of the pure demand spillovers estimated in this paper. Thus, for net paying regions, Cohesion Policy is not only an act of European solidarity but also a rational long-run economic growth policy.
Keywords: C67; D57; R11; R15; R58; 330; Cohesion Policy; Input-Output Analysis; EU Regions; Regional Development